Propriedades mecânicas de painéis produzidos com lascas de madeira em três diferentes comprimentos - Chiromito, Emanoele Maria Santos [UNESP]; De Campos, Cristiane Inácio [UNESP]; Ferreira, Bruno Santos [UNESP]; Christoforo, André Luis; Lahr, Francisco Antonio Rocco (My University, 2016)
The development of technology in panel production and the increased demand for these products, coupled with the increased cost of solid wood with large dimensions, led to the development of engineered wood products industry. Because of this, the aim of this research was to evaluate mechanical properties in static bending of Oriented Strand Board (OSB), Oriented Strand Lumber (OSL) and Laminated Strand Lumber (LSL), produced with Pinus taeda wood and castor oil based polyurethane resin. The influence of the strand lengths (inherent in each type of panel) in its properties of strength and stiffness was evaluated. Bending test was carried out according to EN 310-2000 and ASTM D 198-09 standards for determining the modulus of elasticity and modulus of rupture of the three types of panels. The results of strength (MOR) and stiffness (MOE) in bending for the three types of panels met the minimum requirements of EN 310-2000 standard, and the increase in the length of the strands influenced positively and significantly these properties. LSL panels presented the best results, followed by the OSL and OSB panels, respectively.
Mechanical properties of wood panels produced with wood strands with three different lengths
Keywords: Modulus of elasticity; Modulus of rupture; Pinus taeda; Structural panels